Acute Flaccid Monoplegia After an Asthmatic Attack - Mekmangkonthong, Aphirak; Khusiwilai, Khanittha; Paticheep, Sudathip (Asian Medical Journal and Alternative Medicine, 2022)
Background: Hopkins syndrome is a polio-like paralytic illness following a few days after asthmatic attack. Although very rare, the disease has devastating clinical outcomes. Case Report: The patient was a 4-year-old girl presenting with acute monoplegia of her right arm six days after an event of acute asthmatic attack. Magnetic resonance imaging revealed increased T2 signal intensity within the cord from C1 to C6-7 levels, mainly at anterior horns. The patient did not gain motor power improvement after two years of treatment and follow up. Conclusions: We report a rare case of Hopkins syndrome presented with acute flaccid monoplegia and magnetic resonance imaging pathology. This is the first case report in Southeast Asia